Traumatic Duodenal Injury Presenting as a Slight Retroperitoneal Hematoma around the Treitz ligament: A Case Report - Kiyonaga, Hidetoshi; Aizawa, Kikuo; Miyashita, Kaoru; Morioka, Nobuhiro (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2006)
Duodenal injury in abdominal trauma is relatively rare. Early diagnosis is difficult, compared to other gastrointestinal tract injuries, because the duodenum is located in the retroperitoneum. When this condition is not diagnosed early, serious complications like suture failure may occur postoperatively because of the effects of bile or pancreatic juice. A 45-year old man was admitted for blunt abdominal trauma. An abdominal CT scan did not reveal the presence of air or fluid collection in the retroperitoneal cavity around the duodenum one hour after, the blunt abdominal injury. During an emergency laparotomy for the treatment of other injured organs, a slight hematoma around the Treitz ligament in the retroperitoneum was found. We mobilized the duodenum and found a perforation in the 4th portion of the duodenum. A duodenorrhaphy was subsequently performed. No serious complications occurred during the postoperative course.